Digital Marketing Physiognomy and Their Impact on Marketing Future Products - Yousef Hchaim Al-Taie; Hussein Muhammad Ali Kashkool (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the rapidly evolving digital business landscape, organizations must understand customer behaviors and anticipate market trends to remain competitive. Specific Background: Digital marketing foresight has emerged as a crucial competency, integrating analytical, cognitive, and behavioral capacities that enable marketers to predict and respond to future customer demands. Knowledge Gap: However, there is limited empirical research, particularly in emerging markets such as Iraq, examining how employees’ digital marketing insights directly influence the marketing of future products. Aims: This study investigates the relationship between digital marketing insight dimensions—deep customer knowledge, mental empowerment, digital inspiration, and sensibility—and the marketing of future products within Asiacell Telecommunications Company. Results: Using Structural Equation Modeling (SEM) on 476 valid responses, findings reveal a significant positive correlation between digital marketing insights and future product marketing dimensions, including digital, adaptable, novel, and unexpected products. Novelty: The study introduces empirical evidence on how online customer service employees’ digital awareness translates into innovative and adaptive marketing outcomes. Implications: These results highlight the strategic importance of enhancing employees’ digital foresight to foster sustainable innovation, strengthen competitiveness, and align future product development with evolving customer expectations.Highlight : The study identifies a significant positive relationship between digital marketing insights and marketing of future products. Employee understanding of digital customers and mental empowerment improve innovation and adaptability. Asiacell gains a competitive advantage by developing digital foresight among its customer service employees. Keywords : Digital Marketing Insights, Marketing of Future Products, Digital Customer Service Employees, Asiacell